Quantification of mesoscale variability and geometrical reconstruction of a textile - Gommer, Frank; Brown, Louise P.; Brooks, Richard (Sage, 2015)
Automated image analysis of textile surfaces allowed determination and quantification of intrinsic yarn path variabilities in a 2/2 twill weave during the lay-up process. The yarn paths were described in terms of waves and it was found that the frequencies are similar in warp and weft directions and hardly affected by introduced yarn path deformations. The most significant source of fabric variability was introduced during handling before cutting. These resulting systematic deformations will need to be considered when designing or analysing a composite component. An automated method for three dimensional reconstruction of the analysed lay-up was implemented in TexGen which will allow virtual testing of components in the future.